Criança não pode esperar [manuscrito]; a demanda de mães e suascrianças em condições não urgentes em ambulatório pediátrico de urgênciae emergência - Rose Meire Silva Rati (2009)
The objective of this study was to understand the reasons why mothers search for urgency and emergency attention for children in non urgent conditions in a reference emergency pediatrics hospital of Unique Health System in Belo Horizonte. The qualitative approach has been used as a methodology, having the semi-structured interview and the free observation through time sample as resources to get it. This observation was done on various days and hours when ranking risk prevails. From June to September, 2008, 27 mothers of children classified as little and non urgent were interviewed. The statements were analysed by using the technique of contents analyses. The results showed that the conception of urgency and emergency to themothers is different from the one adopted by the institution. It was clear that most cases classified as little and non urgent by the institution are considered urgent by the mothers, which shows a gap between these mothers feelings and the rationality of the service organization. A sick child can cause various feelings in the mothers, such as anguish, fear, guilt and not always are the professionals prepared to deal with it. The mothers look for urgency and emergency services even when they knowthe case is not urgent, for different reasons among which, fear that the case will worsen, certainty of medical care and technological resources. The interviewed mothers showed not to understand well the risk ranking and the care priority, despite the explanations given by professionals. We observed in this study that reception with risk ranking was done based on clinic-biomedical model, in which the care is centered in the patient complaint and as a form of triage. This work could identify some important aspects, which can lead to reflection on service organization, so that the reception can turn into usual practice, outdoing the hegemonic model towards the centralization of the user.